2006
DOI: 10.2105/ajph.2004.042200
|View full text |Cite
|
Sign up to set email alerts
|

Environmental–Structural Interventions to Reduce HIV/STI Risk Among Female Sex Workers in the Dominican Republic

Abstract: Interventions that combine community solidarity and government policy show positive initial effects on HIV and STI risk reduction among female sex workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
203
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(207 citation statements)
references
References 16 publications
3
203
1
Order By: Relevance
“…50 Recent work in India and the Dominican Republic has shown that promoting empowerment among FSWs at the community and individual levels can greatly improve safer sex negotiation skills, contributing to improved sexual and reproductive health outcomes. 8,51,52 Although few interventions to date have specifically targeted FSWs' noncommercial relationships, some studies suggest that promoting collectivization can improve safer sex norms beyond commercial sexual encounters and can extend into women's personal relationships. 53 Our finding that FSWs with higher sexual decision-making power were less likely to have HIV/STIs provides further evidence in support of HIV/STI prevention interventions addressing relationship power.…”
Section: Discussionmentioning
confidence: 99%
“…50 Recent work in India and the Dominican Republic has shown that promoting empowerment among FSWs at the community and individual levels can greatly improve safer sex negotiation skills, contributing to improved sexual and reproductive health outcomes. 8,51,52 Although few interventions to date have specifically targeted FSWs' noncommercial relationships, some studies suggest that promoting collectivization can improve safer sex norms beyond commercial sexual encounters and can extend into women's personal relationships. 53 Our finding that FSWs with higher sexual decision-making power were less likely to have HIV/STIs provides further evidence in support of HIV/STI prevention interventions addressing relationship power.…”
Section: Discussionmentioning
confidence: 99%
“…Condom use increased in individual SWs and was associated with reduced incident STIs in both arms of the study. However, the likelihood of a brothel adhering to the 100% condom use programme was 10% greater in the policy change area (Kerrigan et al 2003(Kerrigan et al , 2006.…”
Section: Structural Interventionsmentioning
confidence: 93%
“…Starting in the mid-1990s, a decline in HIV prevalence has been noted at antenatal clinics in the capital, Santo Domingoa trend that probably reflects efforts to promote safer commercial sex in the city (Secretaria de Estado de Salud Pública y Asistencia Social de Republica Dominicana, 2005b). For example, condom use increased from 75% to 94% in 12 months among sex workers who participated in a community solidarity prevention project in the capital (Kerrigan et al, 2006).…”
Section: Several Countries Are Making Progress In Controlling Their Ementioning
confidence: 99%